#### Answer

The solution is all real numbers.
Using set notation: {x|x is an element of the real numbers}

#### Work Step by Step

5x - 5 = 3x - 7 +2(x + 1)
First, complete the distributive property on the right side of the equation.
5x - 5 = 3x - 7 + 2x + 2
Then, combine like terms on the right side of the equation. FIrst regroup them so that like terms are together. Note: The sign to the left of a term stays with the term.
5x - 5 = 3x + 2x - 7 + 2
5x - 5 = 5x - 5
Subtract 5x from both sides.
5x - 5x - 5 = 5x - 5x - 5
-5 = -5
Since both sides of the equation are now the same and the variable terms completely subtracted out (leaving no variable term), the solution is all real numbers.